The only girl in the world [compact disc, unabridged] : a memoir - Julien, Maude, 1957-; Gauthier, Ursula (Hachette Audio, 2017)
Maude Julien's parents were fanatics who sought to turn her into the ultimate survivor through constant, elaborate abuse. But she befriended animals and read novels in secret though her parents had forbidden compassion as weakness. When an outsider penetrated her family's paranoid world, Maude seized her opportunity to escape.